Incidence of Hypotension during Recovery from Spinal and Epidural Anesthesia - Atia A1* and Elyagoubi A2 (AlQalam Journal of Medical and Applied Sciences, 2017)
Background: Postoperative hemodynamic complication (hypotension) can occur during recovery from spinal anesthesia. The aim of this study was to evaluate the level of blood pressure during and after applying spinal and epidural anesthesia techniques. Methods: Forty patients were evaluated for hypotension induced by Lidocaine used in spinal or epidural anesthesia approaches. The patients were randomly assigned in the two groups and informed consent was taken. Lidocaine was injected in L4-L5 space using needle No. 23 in the spinal group and needle No. 16 in the epidural group. Results: There was no significant decrease in systemic blood pressure before and after 10 min in both the spinal and epidural groups (p>0.05). There was also no significant difference in systolic blood pressure in the spinal group compared to the epidural group. Conclusion: Appropriate assessment before anesthesia and perioperative adequate monitoring and preparation are important to prevent decrease in blood pressure.